THE INFLUENCE OF THE DISTANCE ON THE RESULTS OF THE WORK GROUP OF VEHICLES FOR THE CARGO TRANSPORTATION BY THE SUPPLIER - E. R. Aytbagina; E. E. Vitvitskiy (Вестник СибАДИ)
The article extends the theory of automobile cargo transportation on the influence of distance on the results of the work group of vehicles. Made the solution the task of operational planning of transportation of bricks on pallets by automobile transport in the city, defined output in tons, ton-km, the production cost in a individual day of work for each distance of the considered range, established the dependence of the production cost from increasing the distance of cargo transportation verified the adequacy of the test process.